Congenital malformations of gastrointestinal tract in children aged less than 5 years of age: A retrospective and prospective study - Dr. Vinila Belum Reddy; Dr. M. Ramani; Dr. Jaya Bhaskar Reddy (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: The spectrum and prevalence of congenital abnormalities of gastrointestinal tract vary in different populations depending upon the environment influences, genetic predisposition and prevalent socioeconomic factors. The aim of this study is to review and analyse the cases registered in the last five years in our centre and study their clinical presentation, spectrum, prevalence and also the histopathological picture.Methods: This cross-sectional descriptive study was taken up in Niloufer Hospital, Hyderabad. This was a 3 year retrospective and 2 year prospective study. All Pediatric surgical specimens and biopsies of children aged less than 5 years received during a period of 5 years were included in the study.Results: During the study period, total 2842 pathological specimens were reviewed, out of which 161 (5.67%) cases were related to GI tract Anomalies. Hirschsprung’s disease was the commonest accounting for about 47.2% of all the anomalies. Together Hirschsprung’s disease, Omphalo mesenteric duct remnants, intestinal atresia’s, duplication cysts and meconium ileus contributed to greater than 75% (¾ ) of the cases. Most of the cases were less than 1 year of age (71%). Male predominance was noted with a male to female ratio of 2.74:1.Conclusion: Congenital and developmental abnormalities of gastro intestinal tract are not very uncommon in the Indian sub continent and these are a cause of significant mortality and morbidity in pediatric age group. This study has highlighted the prevalence and types of congenital anomalies seen in our Geographical area.